The Use of AI as an Assistant of University Students for their Research Proposal - Muhammad Dimas Rinjani Fitra; Kristanti Yuntoro Putri; M Syaichul Muchyidin; Fika Ar-Rizqi Naf’ihima (Institut Agama Islam Negeri Palopo, 2025)
This research examines the role of Artificial Intelligence (AI) as an assistant for university students in drafting their research proposals. Addressing challenges such as ineffective research strategies, time management issues, and writing difficulties, the study explores how AI tools enhance productivity and support academic writing. Using a qualitative approach, data were collected through questionnaires, semi-structured interviews, and observations of university students utilizing AI tools like Grammarly and ChatGPT. The findings reveal that AI tools significantly aid students in generating ideas, structuring proposals, and refining their writing. However, challenges include ethical concerns, the risk of over-reliance on AI, and limitations in addressing complex academic requirements. By understanding students' perceptions and experiences, this research highlights the potential of AI to complement traditional academic support systems, fostering more efficient and effective research proposal development.